Mechanical Behavior and Microstructural Analysis of Molybdenum-TZM Alloy Subjected to Different Annealing Temperature - Muhamad Anas Munawwar Ghazali; Mohd Azhar Harimon; Mohammad Sukri Mustapa (JSE Journal of Science and Engineering, 2020)
Mo-TZM alloy is one of the most famous economic molybdenum-based alloys. The percentage of chemical composition in mass of Mo-TZM alloy are Mo-0.5Ti-0.08Zr-0.03C. By adding some Titanium and Zirconium so that the mechanical properties and recrystallization temperature of molybdenum has been corresponding improvement. The purpose of this study is to determine the effect of different annealing temperature on mechanical properties of Mo-TZM alloy. The samples will be heated at two different temperature which are 1000 oC and 1300 oC in 1 hour and 40 minutes to change their microstructure behavior. The mechanical properties of the sample like hardness will be analyzed by using Vickers Micro hardness test. The force applied is 4.903 N and Vickers micro hardness number is 0.5 HVN for 10 second. Then to observe the microstructure changes, optical microscope and Scanning Electron Microscope (SEM) is be used. At annealing temperature 1000 oC, it show values of hardness is 249.54 VHN and the grain boundary size is 0.0898mm. While at annealing temperature 1300 oC, it show the lowest values of hardness which is 243.55 VHN and the highest grain boundary size which is 0.1068 mm. By doing annealing heat treatment it will decreases hardness values and increases the size of grain boundary